The Corruption of Philosophical Communication by Translation Plagiarism. Issue 3 (13th June 2019) - Dougherty, M. V.
Abstract: Disguised plagiarism often goes undetected. An especially subtle type of disguised plagiarism is translation plagiarism, which occurs when the work of one author is republished in a different language with authorship credit taken by someone else. I focus on the challenge of demonstrating this subtle variety of plagiarism and examine the corruptive influence that plagiarizing articles exert on unsuspecting researchers who later cite them in the downstream literature as genuine products of research. I conclude by arguing that an open discussion of plagiarizing articles in philosophy is necessary for maintaining the reliability of the body of published research and for restoring integrity to scholarly communication.